2013
DOI: 10.1016/j.gr.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Middle–Late Paleozoic Australia–Asia convergence and tectonic extrusion of Australia

Abstract: Recent and new paleomagnetic data from ignimbrite-rich Carboniferous successions of the western Tamworth Belt, Southern New England Orogen, eastern Australia, show a northward excursion over~30°. Paleozoic data from the Australian craton and Tasman Orogenic System (TOS) suggest an Early Devonian start. At the middle-late Visean peak, the central New Guinean promontory of the Australian craton reached 30°-40°N, within the latitude range of the western Central Asian Orogenic Belt (CAOB). Devonian-Carboniferous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 605 publications
(913 reference statements)
2
21
0
Order By: Relevance
“…Model M4b, and to a lesser extent Model M2 (Figures b–b), shows higher values for vorticity in the Harts Range area compared with all remaining models (Table ). These vorticity values can be explained by the west directed protrusion and flow of crustal material inside the weak wedge (Figures b and b), similar to the channel flow extrusion documented in the Himalaya‐Tibetan Plateau (Beaumont et al, ; Bird, ; Godin et al, ) and hypothesized by Klootwijk () for the intraplate Australian continent. This movement of material inside the wedge would imply both sinistral and dextral strike‐slip kinematics along the northern and southern boundaries of the wedge, respectively (Figure b–b and ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Model M4b, and to a lesser extent Model M2 (Figures b–b), shows higher values for vorticity in the Harts Range area compared with all remaining models (Table ). These vorticity values can be explained by the west directed protrusion and flow of crustal material inside the weak wedge (Figures b and b), similar to the channel flow extrusion documented in the Himalaya‐Tibetan Plateau (Beaumont et al, ; Bird, ; Godin et al, ) and hypothesized by Klootwijk () for the intraplate Australian continent. This movement of material inside the wedge would imply both sinistral and dextral strike‐slip kinematics along the northern and southern boundaries of the wedge, respectively (Figure b–b and ).…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the westward tectonic stress influences on central Australia orogenesis have largely been ignored. Studies by Roberts and Houseman (2001), Klootwijk (2013), and Kröner et al (2016) correlate intraplate reactivation of central Australia with the mainly N-S convergence between Gondwana and Laurasia, forming the Qinling Orogen in the north (Figure 3a). Using numerical models, Roberts and Houseman (2001) showed that rotation of the north Australian block induced simultaneous extension of the Canning Basin in NW Australia and N-S convergence within an area of lithospheric weakness in central Australia.…”
Section: Current Models For the Formation Of The Asomentioning
confidence: 98%
See 1 more Smart Citation
“…1b, c). The origin of these (~E-W) structural features is controversial (Burton, 2010;Glen et al, 2013;Klootwijk, 2013;Burton and Trigg, 2014;Glen et al, 2014), partly because of the very limited exposure of the Thomson Orogen in central Queensland and northwestern New South Wales (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Exceptions to this approach include linking intraplate deformation in central Australia in the late Paleozoic Alice Springs Orogeny to megakinking in the Lachlan Orogen (Powell, 1984b) and tectonic extrusion in eastern Australia linked to Australian-Asian collision (Klootwijk, 2013). Paleomagnetic data suggest that there has been a 40° anticlockwise rotation between the North Australian Craton and an amalgam of the West and South Australian cratons along the southern margin of the Musgrave Block in central Australia in the interval 650 to 550 Ma (Li and Evans, 2011).…”
Section: Introductionmentioning
confidence: 99%